Leaf decomposition in a cool‐temperate broad‐leaved forest established on serpentine soil on Mount Oe, Japan. Issue 5 (5th September 2019) - Sato, Kai; Nakamura, Ryosuke; Kajino, Hirofumi; Kawai, Kiyosada; Nakai, Wataru; Saito, Haruka; Okada, Naoki
Abstract: Serpentine ecosystems are characterized by soil with high heavy metal and low nutrient content, both of which are likely to influence the rate of leaf decomposition. Here, we report how leaf chemistry and the microbial community influence the leaf decomposition rate in a serpentine ecosystem. Fresh Clethra barbinervis and Quercus serrata leaves collected from serpentine and non‐serpentine sites in cool‐temperate forests were placed at both sites for several months, after which changes in leaf mass were determined. The N concentration in the initial Q. serrata leaves from the serpentine site was lower than in those from the non‐serpentine site. The Ni concentration in the initial C. barbinervis leaves from the serpentine site was higher than in those from the non‐serpentine site. The leaves from the serpentine site decomposed slower than those from non‐serpentine sites for both species. Although we expected that serpentine soil would have a negative influence on microbial decomposers, the Q. serrata leaves placed in the serpentine site decomposed faster than those placed in the non‐serpentine site, suggesting that the serpentine soil had no adverse effect on microbial decomposers. However, microbial respiration and biomass in an in vitro experiment were not high in the leaves decomposed on serpentine soil. Future work should reveal the mechanism behind this contradiction. Our results suggest that the change of leaf quality is key to understanding the leaf decomposition rate in a serpentine ecosystem. Abstract : The leaves from the serpentine site decomposed slower than those from non‐serpentine sites for Clethra barbinervis and Quercus serrata . Although we expected that serpentine soil would have a negative influence on microbial decomposers, the Q. serrata leaves placed in the serpentine site decomposed faster than those placed in the non‐serpentine site, suggesting that the serpentine soil had no adverse effect on microbial decomposers.